2023
DOI: 10.1039/d3ce00162h
|View full text |Cite
|
Sign up to set email alerts
|

The chemical stability of ZIF-8 in aldehyde under air conditions

Abstract: The chemical stability of zeolitic imidazolate framework-8 (ZIF-8) in water, acid, base and organic solvent has been widely investigated. Nevertheless, whether it is stable in aldehydes that are the common...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…However, the contribution to this intensity reduction due to an etching effect on the NPs' surface produced by the aldehyde molecules cannot be completely discarded. 28 Fig. 1 (a) Scheme of biomolecule encapsulation into ZIF-8.…”
Section: Biomolecule Encapsulation Within Zif-8 Nanoparticlesmentioning
confidence: 99%
“…However, the contribution to this intensity reduction due to an etching effect on the NPs' surface produced by the aldehyde molecules cannot be completely discarded. 28 Fig. 1 (a) Scheme of biomolecule encapsulation into ZIF-8.…”
Section: Biomolecule Encapsulation Within Zif-8 Nanoparticlesmentioning
confidence: 99%
“…In addition, the abundance of N groups and unsaturated cations on the surface of ZIF-8 makes it easy to generate more active sites. More importantly, ZIF-8 has high chemical and thermal stability due to the strong coordination reaction between anionic ligands and metal ions in neutral and alkaline media [30]. Li et al [31] found that ZIF-8@TiO 2 improved the catalytic degradation ability of tetracycline by TiO 2 .…”
Section: Introductionmentioning
confidence: 99%